Construction of gold-siRNANPR1 nanoparticles for effective and quick silencing of NPR1 in Arabidopsis thaliana. Issue 33 (20th May 2020) - Lei, Wen-Xue; An, Zi-Shuai; Zhang, Bai-Hong; Wu, Qian; Gong, Wen-Jun; Li, Jin-Ming; Chen, Wen-Li
Abstract : Gold nanoparticles (AuNPs) have been widely used as gene silencing agents and therapeutics for treatment due to their high transfection efficiency and lack of cytotoxicity, but their roles in gene silencing in plants have not yet been reported. Abstract : In recent years, gold nanoparticles (AuNPs) have been widely used as gene silencing agents and therapeutics for treatment of cancers due to their high transfection efficiency and lack of cytotoxicity, but their roles in gene silencing in plants have not yet been reported. Here, we report synthesis of AuNPs-branched polyethylenimine and its integration with the small interfering RNAs (siRNA) of NPR1 to form a AuNPs-siRNA NPR1 compound. Our results showed that AuNPs-siRNA NPR1 was capable of infiltrating into Arabidopsis cells. AuNPs-siRNA NPR1 silenced 80% of the NPR1 gene in Arabidopsis . Bacteriostatic and ion leakage experiments suggest that the NPR1 gene in Arabidopsis leaves was silenced by AuNPs-siRNA NPR1 . In Columbia-0 plants, compared with the control group treated with buffer solution, the AuNPs-siRNA NPR1 treatment significantly increased the number of colonies and cell death, and the leaves turned yellow, similar to the phenotype of the npr1 leaves. These results indicated this AuNPs-siRNA NPR1 silencing the NPR1 gene method is simple, effective and quick (3 days), and a powerful tool to study gene functions in plants.